Bubbling in a power electronic inverter: Onset, development and detection. (November 2017) - Avrutin, Viktor; Morcillo, Jose D.; Zhusubaliyev, Zhanybai T.; Angulo, Fabiola
Abstract: Power electronic DC/AC converters (inverters) play an important role in modern power engineering for a broad variety of applications including solar and wind energy systems as well as electric and hybrid cars drives. It is well known that the waveform of the output voltage (or current) of an inverter may be significantly distorted by phase restricted high frequency oscillations, frequently referred to as bubbling. However, the reasons leading to the appearance of this undesired effect are still not completely understood. Considering as an example a 2D model of a PWM H-bridge single-phase inverter, the present paper reports the appearance of two different kinds of bubbling. In the first case, the appearance of bubbling occurs suddenly and is related to the change of periodicity. We show that high-periodic, quasiperiodic and chaotic oscillations may exhibit bubbling, and also that solutions with and without bubbling may coexist. In the second case, the appearance of bubbling occurs gradually in the parameter domain where the investigated system undergoes border collisions of so-called persistence type. As a result, the appearance of the bubbling of the second kind does not change the periodicity of the motion but nevertheless disturbs the waveform. We discuss some differences in the properties of the second kind of bubbling from the first one, and present numerical techniques for its detection.